THE EFFECTIVENESS OF IMPLEMENTATION OF CROSSFIT TOOLS IN THE PROCESS OF PHYSICAL EDUCATION OF HIGH SCHOOL PUPILS - Rymar, Olga; Sorokolit, Nataliya; Solovey, Alla; Khanikiants, Olena; Malanchuk, Halyna; Petryna, Roman (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
There is justified in the article the importance of the need to improve physical education process for high school students with CrossFit tools.There have occurred positive changes in high school students’ dynamics in the EG in functional indicators and physical preparation in the experiment condition.The optimization of physical education process for high school pupils with CrossFit tools. There were observed the indicators of physical condition of organism, physical preparation and experimentally checked the effectiveness of the program with CrossFit tools implemented into physical education process. There were 63 pupils as participants in the research (boys, 16 years old). Analysis of literature sources, phyiological methods of research, pedagogical researches (control norms passing); pedagogical experiment; mathematical statistics methods. There is presented and scientifically justified program of CrossFit tools implementation into physical education lessons for high scool pupils. The content of progam includes combination of power and aerobic exercises, stretching, and exercises to restore breath and to relax muscles. The elaborated program is implemented into studying program and there was proved its effectiveness. The results of research have shown its positive impact on fucntional indicators and physical preparation of hish school pupils, that is proved by mathematical statistics methods.